Choroidal Neovascularization in Primary Membranous Nephropathy - Gambato, Tommaso (Am J Case Rep, 2020)
Patient: Male, 61-year-old Final Diagnosis: Choroidal neovascularization Symptoms: Decrease in the visual acuity • metamorphopsia Medication:— Clinical Procedure: — Specialty: Nephrology • Ophthalmology OBJECTIVE: Rare co-existance of disease or pathology BACKGROUND: We describe the retinal findings in a patient affected by primary membranous nephropathy (MN). CASE REPORT: A 61-year-old man presented with a 3-month history of metamorphopsia and decreased visual acuity in both eyes. He was affected by nephrotic syndrome in primary MN and treated with systemic corticosteroids. Dilated fundus examination, optical coherence tomography, and fundus fluorescein angiography revealed the presence of peripapillary choroidal neovascularization (CNV) in the right eye and peripheral CNV in the left eye. A serous retinal detachment with gravitational tract was also observed in both eyes. The patient was treated with intravitreal bevacizumab in the right eye and oral corticosteroids were discontinued. Both eyes achieved a morphological and functional improvement. CONCLUSIONS: We present the first case of primary MN associated with CNV, possibly secondary to central serous chorioretinopathy, successfully treated with intravitreal bevacizumab and discontinuation of oral corticosteroids.